PELATIHAN CALON KADER POSYANDU REMAJA DI DESA KARANGSALAM KIDUL KEDUNGBANTENG BANYUMAS - Sari, Hesti Permata; Sulistyaning, Afina Rachma; Farida, Farida (Jurnal of Community Health Development, 2023)
Adolescence is the second period of growth and development after toddlerhood. Teenagers are faced with nutritional problems that prevent them from optimally reaching their potential. Prevention can be done by early detection of nutritional problems by peers through Youth Posyandu. This activity aims to increase knowledge and attitudes related to nutrition and skills in measuring nutritional status in prospective Youth Posyandu cadres in Karangsalam Kidul, Kedungbanteng, Banyumas using nutrition education methods and training in measuring nutritional status. Data analysis used the dependent t-test. The result is an increase in the knowledge, attitudes, and skills of prospective Youth Posyandu cadres. This education and training are expected to create Youth Posyandu cadres who care about adolescent nutrition.